2021
DOI: 10.3390/cancers13246391
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Polyamine Pathways in Human Pancreatic Tumor Progression and Effects of Polyamine Blockade on Tumor Microenvironment

Abstract: Pancreatic cancer is the fourth leading cause of cancer death. Existing therapies only moderately improve pancreatic ductal adenocarcinoma (PDAC) patient prognosis. The present study investigates the importance of the polyamine metabolism in the pancreatic tumor microenvironment. Relative mRNA expression analysis identified differential expression of polyamine biosynthesis, homeostasis, and transport mediators in both pancreatic epithelial and stromal cells from low-grade pancreatic intraepithelial neoplasia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Recently, polyamine-related aberrance was reported in PC. A transcriptomics study found that the gene expression of proteins associated with polyamine synthesis pathways is associated with the prognosis of PC [ 46 ]. In addition, polyamine concentration patterns accurately distinguished among PC, chronic pancreatitis, and HC samples [ 47 ].…”
Section: Applications For Cancer Biomarker Discoverymentioning
confidence: 99%
“…Recently, polyamine-related aberrance was reported in PC. A transcriptomics study found that the gene expression of proteins associated with polyamine synthesis pathways is associated with the prognosis of PC [ 46 ]. In addition, polyamine concentration patterns accurately distinguished among PC, chronic pancreatitis, and HC samples [ 47 ].…”
Section: Applications For Cancer Biomarker Discoverymentioning
confidence: 99%
“…Interestingly, although combined DFMO (1% w/v) and Trimer PTI (1.8 mg/kg) conferred significant survival benefits in the orthotopic Pan02 model of gemcitabine-resistant pancreatic cancer, it did not further reduce tumor burden when compared to DFMO or PTI alone [31]. Nakkina et al increased the Trimer44NMe dosage to 4 mg/kg, (DFMO: 0.25% w/v) and observed a significant increase in survival, reduction in Pan02 pancreatic tumor burden, and increase in co-stimulatory marker CD86 expression when compared to either treatment alone [32].…”
Section: Dfmo and Trimer44nme Reduce Immunosuppression And Sensitize ...mentioning
confidence: 99%
“…Polyamines are involved in various physiological functions, such as cell division and proliferation, and nucleic acid and protein synthesis; studies have also determined their roles in cancer cells [29][30][31]. Since we identified several polyamine metabolites in the PC2 axis in the PCA analysis (Figure 1), we also analyzed the polyamine synthesis pathway.…”
Section: Polyamine Metabolism Is Altered In Ad-cafsmentioning
confidence: 99%